ABDURRAHMAN WAHID’S CONTRIBUTION FOR INTER-RELIGIOUS DIALOGUE IN INDONESIA - Achmad Munjid (IAIN Manado, 2020)
Abstract: By understanding the historical development of inter-religious dialogue in Indonesia and its global setting since 1970s from rhetoric strategy to meaningful encounter, this paper seeks to situate important contribution of Abdurrahman Wahid’s legacy besides those of other key figures in the field. The paper will critically analyze how and why Abdurrahman’s ideas and works in inter-religious dialogue are intertwined with his family and personal biography, socio-political context of the New Order and after and his traditionalist Muslim background. In particular, Abdurrahman’s reinterpretation of Islamic texts, doctrine and tradition will be discussed in the light of his vision for Indonesian democracy. His notion of religious pluralism, tolerance, peaceful co-existence, mutual understanding, and indigenization of Islam will be explained as intellectual and political enterprises by which he navigates and challenges all forms of injustices especially created by the New Order’s politics of fear, exploitation of anti-Communist sentiment, ethnicity, religion, race and inter-social groups (SARA) and developmentalist ideology under Suharto’s presidency. His engagement in inter-religious dialogue will be read against the developing context of the New Order’s post-1965 politics of religion to the 1990s re-Islamization, the persistent growth of Islamic sectarianism, exclusivism, and identity politics that eventually results in interreligious tension and mutual suspicion, especially between Muslims and Christians. The paper seeks to understand how and why Abdurrahman Wahid as a prominent leader of Muslims as majority group explores inter-religious dialogue as a means by which religious communities are supposed to contribute and work together in overcoming common problems faced by the society. His commitment for and advocacy of the local culture, tradition, minority rights, and Islamic inclusivism will be understood as his struggle as statesman, religious leader, public intellectual and social activist for the creation of equality and justice for all citizens and human dignity in accordance with Islamic teaching and principles of democracy.Keywords: Inter-religious Dialogue, Religious Pluralism, Indigenization of Islam, Islamic Sectarianism, Identity Politics, Democracy. Abstrak: Dengan memahami perkembangan historis dialog antar-agama di Indonesia serta latar globalnya sejak 1970-an dari strategi retoris menjadi perjumpaan yang bermakna, paper ini akan menempatkan sumbangan warisan Abdurrahman Wahid bersama para tokoh kunci lainnya dalam bidang ini. Secara kritis paper ini akan menganalisis bagaimana dan kenapa gagasan serta karya Abdurrahman Wahid dalam dialog agama terjalin erat dengan biografi pribadi dan keluarganya, konteks sosial-politik Orde Baru dan sesudahnya serta latar belakang Islam tradisional yang menjadi basisnya. Secara khusus, penafsiran ulang Abdurrahman Wahid terhadap teks, doktrin, dan tradisi akan didiskusikan dalam kaitannya dengan visinya tentang demokrasi Indonesia. Pengertiannya tentang pluralism agama, toleransi, hidup berdampingan secara damai, saling memahami, dan pribumisasi Islam akan dijelaskan sebagai ihtiar intelektual dan politisnya yang dengan itu ia melakukan navigasi dan menggugat segala macam bentuk ketidakadilan khususnya yang muncul sebagai akibat dari politik ketakutan Orde Baru, eksploitas terhadap sentiment anti-Komunis, SARA dan ideologi pembangunan selama masa Suharto. Keterlibatannya dalam dialog antar-agama akan dibaca dalam kaitannya dengan perkembangan konteks politik agama pasca-1965 yang dilakukan Orde Baru hingga re-Islamisasi 1990an dan kian mengerasnya Islamisme, ekslusivisme serta politik identitas yang akhirnya mengakibatkan ketegangan hubungan antar-agama dan saling curiga, khususnya antara Muslim dan Kristen. Paper ini berusaha untuk memahami bagaimana dan mengapa Abdurrahman Wahid sebagai pemimpin terkemuka Islam sebagai kelompok mayoritas mengeksplorasi dialog antar-agama sebagai sarana bagi komunitas agama untuk berkontribusi dan bekerjasama satu sama lain dalam mengatasi problem bersama yang dihadapi masyarakat. Komitmen serta pembelaannya terhadap budaya lokal, tradisi, hak-hak minoritas dan inklusivisme Islam akan dipahami sebagai bagian dari perjuangannya sebagai seorang negarawan, pemimpin agama dan intelektual publik serta aktivis sosial dalam upaya untuk mewujudkan kesetaraan dan keadilan bagi setiap warga negara serta martabat bagi semua manusia sesuai dengan ajaran Islam dan prinsip-prinsip demokrasi.Kata kunci: Dialog Antar-agama, Pluralism Agama, Pribumisasi Islam, Sektarianisme Islam, Politik Identitas, Demokrasi.